2010
DOI: 10.1302/0301-620x.92b9.23663
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of revision total hip replacement for infection after grading according to a standard protocol

Abstract: Periprosthetic infection following total hip replacement can be a catastrophic complication for the patient. The treatments available include single-stage exchange, and two-stage exchange. We present a series of 50 consecutive patients with a diagnosis of infected total hip replacement who were assessed according to a standardised protocol. Of these, 11 underwent single-stage revision arthroplasty with no recurrence of infection at a mean of 6.8 years follow-up (5.5 to 8.8). The remaining 39 underwent two-stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
84
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(95 citation statements)
references
References 35 publications
5
84
0
6
Order By: Relevance
“…According to previous reports (Table 3), some surgeons routinely perform one-stage revision THAs, with infection control rates in six studies reported to be 77-100 % [1,2,12,22,23,25]. Others, including our study, selected one-stage revision THA depending on patient requirements and showed infection control rates of 76-100 % in the eight studies [13,[15][16][17][18][19]26]. These rates were similar to those reported in studies only performing onestage revision THAs.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…According to previous reports (Table 3), some surgeons routinely perform one-stage revision THAs, with infection control rates in six studies reported to be 77-100 % [1,2,12,22,23,25]. Others, including our study, selected one-stage revision THA depending on patient requirements and showed infection control rates of 76-100 % in the eight studies [13,[15][16][17][18][19]26]. These rates were similar to those reported in studies only performing onestage revision THAs.…”
Section: Discussionsupporting
confidence: 86%
“…First, the study sample size was small, involving only 55 individuals. Obtaining a large series from a single institution is difficult, and there have been only five literature reports involving relatively large patient series (>50 patients) from a single institution [15][16][17][18][19]. We considered an analysis from a single The values show the mean (range)…”
Section: Discussionmentioning
confidence: 99%
“…Baseline demographic information of cases and controls is shown in Table 1. For cases, the median duration from joint insertion until first debridement (joint age) was 14 days (interquartile range (IQR) [12][13][14][15][16][17][18][19][20]. The median duration of symptoms until debridement was 4 days (IQR 3-9).…”
Section: Resultsmentioning
confidence: 99%
“…This improvement was not significantly different to that seen in control patients with no PJI and is similar to results of +33 and +39.1 reported in two previous studies examining treatment of PJI with mainly prosthesis exchange. 15,16 Other studies have reported mean post-treatment HHS after treatment of PJI with prosthesis exchange at between 69 and 84 17 and after debridement and prosthesis retention at 79. 9 The mean post-arthroplasty HHS of 68.5 seen in cases in this study is at the lower end of these scores; however, adequate comparison is difficult as these studies do not report pre-arthroplasty HHS and administered the score much later than in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Oussedik et al reported on the only series using a hybrid cemented technique, in which the acetabular component relied on cementless fixation, whereas the femoral stem was inserted with antibiotic cement. At a mean followup of 6.8 years, the authors reported no recurrent infections and 100% component retention in 11 patients with chronic PJI [23] treated with a single-stage exchange arthroplasty in their total cohort of 50 patients with infected total hips treated with a standardized protocol. In contrast, much has been written in the literature on the outcomes of the one-stage procedure when both components are cemented.…”
Section: Discussionmentioning
confidence: 95%